Socratic approach for unlocking creative potential in undergraduate research students - Ng,Wenfa (PeerJ Preprints, 2017)
The final year research project aims to introduce undergraduates to scientific research as well as encourage them to think creatively and critically about problems from different angles. However, most courses in earlier parts of the curriculum focus on well defined problems with clear answers; thus, a huge gap exists between a research project’s desired educational outcomes and the students’ preparation. As a result, students experience significant difficulties in handling ambiguities (i.e., no defined answers) inherent in research, which leads to lack of motivation or trepidation at their projects. Is the above due to students’ lack of creativity? Or does it have more to do with the difficulty of sparking students’ imagination? One possibility for igniting students’ imagination and fascination for their chosen research topic is in using common lab observations and experiences to unlock students’ creative potential. In this abstract preprint, I describe a simple pedagogical tool for helping ignite creative and critical thinking processes in students. Specifically, the Socratic approach of question and answer, used in guiding students to answer their own questions rather than having answers provided to them, helped initiate, in the students, deductive and inductive thinking processes critical to tackling any research problem. This also helps increase students’ self confidence in problem solving. More importantly, the tentative steps taken in independent thinking also helped debunk their misconception that there exists a single correct answer for every research question. Collectively, through simple pedagogical tools such as question and answer, students can be guided to explore different perspectives in problem solving; thus, improving their creative and critical thinking skills.
Keywords: Socratic approach; question and answer; final year project; critical thinking; research project